Mixed marriages: intermarriage and group identity in the Second Temple period - Frevel, Christian (Library of Hebrew Bible/Old Testament studies, 2011)
Preface -- List of Contributors -- Abbreviations -- Introduction: Christian Frevel: The Discourse on Intermarriage in the Hebrew Bible -- Chapter 1: Christian Frevel and Benedikt J. Conczorowski: Deepening the Water: First Steps to a Diachronic Approach on Intermarriage in the Hebrew Bible -- Chapter 2: Katherine E. Southwood: An Ethnic Affair? Ezra's Intermarriage Crisis against a Context of "Self-Ascription" and "Ascription of Others" -- Chapter 3: Ralf Rothenbusch: The Question of Mixed Marriages between the Poles of Diaspora and Homeland: Observations in Ezra -- Nehemiah -- Chapter 4: Juha Pakkala: Intermarriage and Group Identity in the Ezra Tradition (Ezra 7-10 and Neh 8) -- Chapter 5: Benedikt J. Conczorowski: All the same as Ezra? Conceptual Differences between the Texts on Intermarriage in Genesis, Deuteronomy 7 and Ezra -- Chapter 6: Jan Clauß: Understanding the Mixed-Marriages of Ezra-Nehemiah in the Light of Temple-Building and the Book's Concept of Jerusalem -- Chapter 7: Karen S. Winslow: Mixed Marriage in Torah Narratives -- Chapter 8: Yonina Dor: From the Well in Midian to the Baal of Peor: Different Attitudes to Marriage of Israelites to Midianite Women -- Chapter 9: Gary N. Knoppers: "Married into Moab": The Exogamy Practiced by Judah and his Descendants in the Judahite Lineages -- Chapter 10: Sebastian Grätz: The Question of "Mixed Marriages" (Intermarriage): the Extra-Biblical Evidence -- Chapter 11: Armin Lange: Mixed Marriages and the Hellenistic Religious Reforms -- Chapter 12: Christian Frevel: "Separate Yourself From the Gentiles" (Jub. 22:16): Intermarriage in the Book of Jubilees -- Chapter 13: Hannah Harrington: Intermarriage in Qumran Texts: The Legacy of Ezra-Nehemiah -- Chapter 14: Karen S. Winslow: Moses' Cushite Marriage: Torah, Artapanus, and Josephus -- Chapter 15: Claudia Camp: Feminist- and Gender-Critical Perspectives on the Biblical Ideology of Intermarriage -- Index of References -- Index of Authors